Trauma as a neglected etiological factor of mental disorders - Dimitrijevic Aleksandar (Sociologija, 2015)
Throughout the history of mental health care field, trauma was prescribed different and frequently opposing roles. In psychoanalysis, the attitude toward trauma was ambiguous: it was considered a crucial factor, but at the same time its role could happen to be minimized. In biological psychiatry, it is seen as a dominant cause of some disorders and completely irrelevant for the others. In this paper, two issues are discussed: frequency of traumatic events in general population and among persons with mental disorders; and hypothesized intrapsychic mechanisms that lead to detrimental consequences of trauma on mental health. It is advocated that prevention of early, especially attachment, trauma should be the focus of our work in dealing with mental disorders.